(untitled) (Bangladesh Journal of Botany, 2011)
Alocasia fallax Schott and A. odora (Roxb.) Koch (Araceae) were investigated cytogenetically to confirm their taxonomic status. There is no report of 2n chromosome number for A. fallax in the available literature and internet information. Therefore the 2n chromosome number (2n = 28) found in this study is probably the first report for A. fallax. Alocasia odora showed exactly double 2n chromosome number (2n = 56) from A. fallax. In addition to chromosome number, the other karyotypic features of A. odora were exactly double for that of A. fallax. The centromeric formulae of A. fallax was 24 m + 4 sm whereas it is just double in A. odora. Total length of 2n chromosome complement of A. odora (62.58 μm) was almost double to A. fallax. The range of chromosomal length of the two species was almost same. Moreover, A. odora plant is much taller than A. fallax. All of these data suggests that A. odora might be an autotetraploid of A. fallax which in course of evolution had undergone some changes in GC-rich repeats. Key words: Alocasia; CMA; Karyotype analysis DOI: http://dx.doi.org/10.3329/bjb.v40i1.7998 Bangladesh J. Bot. 40(1): 53-56, 2011 (June)